Analisis Produktivitas Penggunaan Alat Berat Terhadap Biaya dan Waktu Pada Pembangunan Jalan Lingkar Cipanas - Elsa Hildiani Fitriansyah; Ganjar Jojon Johari (Institut Teknologi Garut, 2026)
The construction of the Cipanas Ring Road alternative route, located in Tarogong Kaler District, Garut Regency, involves the use of heavy equipment such as excavators, bulldozers, vibrator rollers, and dump trucks for embankment work. Each piece of equipment has its own advantages, disadvantages, and capacities, which can affect both the cost and duration of each project phase. The method used in this study is quantitative, as it involves the use of numerical data and statistics for measurable data collection and analysis.The issue analyzed is to determine the productivity of heavy equipment usage and the operational rental costs of the equipment during the embankment work on the Cipanas Ring Road construction project. The goal is to assess the comparison between the planned productivity calculations of the heavy equipment and the actual results observed in the field. This is done by recalculating the productivity of the equipment using the standard formulas established by the Garut Regency Public Works and Housing Office (PUPR).By doing so, we can compare the cost and time estimates in the field with those calculated by the researcher. The research findings show that the actual costs and duration in the field were higher than those estimated in the analysis. The analytical results indicated a requirement of 24 days (4 weeks) with a cost of Rp.291,991,360.00, whereas the actual field implementation took 70 days (10 weeks) with a cost of Rp.644,000,000.00.